Analysis of Factors Affecting the Stock Prices of Consumer Goods and Trade And Service Sectors on the Indonesia Stock Exchange - Muhammad Iqbal Harahap; Isfenti Sadalia; Khaira Amalia Fachrudin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to examine the variables that affect stock prices in the commerce and service and consumer products industries that are listed on the Indonesia Stock Exchange. This research study is quantitative in nature. The information was taken from annual and financial reports that were posted on the websites of the individual companies as well as the Indonesia Stock Exchange's official website (www.idx.co.id). The population consists of all 137 consumer products, commerce, and service businesses that were listed on the Indonesia Stock Exchange between 2009 and 2013. Seventy-seven businesses satisfied the sample requirements based on preset criteria. Multiple linear regression analysis was used to examine the data. The findings demonstrate that the three sets of variables—systematic risk, macroeconomic indicators, and firm fundamentals—all significantly and favorably affect stock prices at the same time. Stock prices are positively and significantly impacted by the following factors, in part: Return on Equity (ROE), Earnings per Share (EPS), Book Value (BV), Net Profit Margin (NPM), and inflation. In contrast, the market beta, GDP, exchange rate, and BI rate have no discernible effects, but the debt to equity ratio (DER) has a negative and substantial influence. With an Adjusted R Square value of 62.4%, the study's independent variables may account for a significant portion of stock price fluctuations, with additional factors outside the model influencing the remaining 37.6%.